(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
The candy bass, Liopropoma carmabi, is registered for the rst time from the Colombian Caribbean, based in two juvenile specimens 18.8-25.0 mm standard length, caught in August 2003 using Submerged Articial Devices located at Taganga and Gaira bays in the Santa Marta region.